The feasibility of regional television (RTV) in South Africa : a study of the official process towards the issuing of licenses for RTV and subsequent developments - Robinson, F. J. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2007.